Protest Under Uncertainty: Evidence from a Survey Experiment. Issue 2 (17th February 2022) - Matejova, Miriam; Merkley, Eric
ABSTRACT : Environmental disasters generate uncertainty, which is a crucial element of post-disaster political dynamics. Does communication of uncertainty affect public willingness to participate in political activism? This article first provides a content analysis of news coverage to show that uncertainty framing is prevalent in the aftermath of environmental disasters. The article then examines the effect of such uncertainty on public willingness to protest, presenting a survey experiment of over 3, 600 Americans recruited through Amazon Mechanical Turk. In theory, uncertainty framing may trigger emotions like anxiety, which reduce people's willingness to engage in protest. Since in environmental communication uncertainty frames are often used to reify the status quo, which is more easily compatible with conservative beliefs, the dampening effect should be stronger among those who are ideologically conservative. Our experiment confirms the latter expectation but does not find support for the former. These results help explain why some protest coalitions may have more breadth than others after environmental disasters.